Sleep apnea screening is uncommon after stroke - Brown, Devin L. (Sleep Med, 2018)
OBJECTIVE/BACKGROUND: To assess (1) pre and post-stroke screening for sleep apnea (SA) within a population-based study without an academic medical center, and (2) ethnic differences in poststroke sleep apnea screening among Mexican Americans (MAs) and non-Hispanic whites (NHWs). PATIENTS/METHODS: MAs and NHWs with stroke in the Brain Attack Surveillance in Corpus Christi project (2011–2015) were interviewed shortly after stroke about the pre-stroke period, and again at approximately 90 days after stroke in reference to the post-stroke period. Questions included whether any clinical provider directly asked about snoring or daytime sleepiness or had offered polysomnography. Logistic regression tested the association between these outcomes and ethnicity both unadjusted and adjusted for potential confounders. RESULTS: Among 981 participants, 63% were MA. MAs in comparison to NHWs were younger, had a higher prevalence of hypertension, diabetes, and never smoking, a higher body mass index, and a lower prevalence of atrial fibrillation. Only 17% reported having been offered SA diagnostic testing pre-stroke, without a difference by ethnicity. In the post-stroke period, only 50 (5%) participants reported being directly queried about snoring; 86 (9%) reported being directly queried about sleepiness; and 55 (6%) reported having been offered polysomnography. No ethnic differences were found for these three outcomes, in unadjusted or adjusted analyses. CONCLUSIONS: Screening for classic symptoms of SA, and formal testing for SA, are rare within the first 90 days after stroke, for both MAs and NHWs. Provider education is needed to raise awareness that SA affects most patients after stroke and is associated with poor outcomes.